Decreases in scabies and lice cases among the pediatric and adult populations during COVID‐19. Issue 5 (20th July 2022) - Bonanno, Marianne; Lee, Olivia S.; Sayed, Christopher
Abstract: The influence of the nationwide lockdown orders during the COVID‐19 pandemic on the transmission of scabies and lice remains unknown. We conducted a cross‐sectional study utilizing UNC patient registry i2b2 to investigate monthly cases and prescriptions for scabies and lice in adult and pediatric patients in North Carolina. There were significant decreases in the cases and prescriptions for scabies and lice in the pediatric and adult populations. These results provide early insights on how COVID‐19 pandemic lockdown orders affected the prevalence of these two conditions and suggest that physical distancing measures reduce transmission of these parasitic conditions.